Eribulin Effectiveness and Safety in Metastatic Triple-Negative Breast Cancer: A Narrative Review - Meriyani, Herleeyana; Sanjaya, Dwi Arymbhi; Juanita, Rr. Asih; Siada, Nyoman Budiartha; Chusna, Nurul; Ketupapa, Florentina Gabriela (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Triple-negative breast cancer is an aggressive and poor prognosis subtype of breast cancer. Eribulin has shown promise in the treatment of metastatic triple-negative breast cancer (mTNBC). This review aimed to provide a specific description, evidence, and discussion of the efficacy and safety of eribulin both as monotherapy and in combination with another agent in patients with mTNBC. The search was conducted in five databases (PubMed, ScienceDirect, PLoS One, Wiley Online Library, and Cochrane Library) towards published articles during the 2013-2023 period. A total of 237 articles were identified. After removing 69 duplicates, 168 articles underwent the screening process and 10 articles met the research criteria. Eribulin monotherapy effectiveness profile includes: overall survival (10.8-17.6 months), progression-free survival (2.8-3.2 months), partial response (21.0%-58.7%), progressive disease (15.5% -47.0%), and stable disease (28.8%-32%). However, there were no cases of complete response. Combination of eribulin with other agents' effectiveness profiles includes: overall survival (8.3-14.5 months), PFS (2.6-8.1 months), partial response (31.8-76.0%), complete response (2.4-8%), progressive disease (8.0-28%), and stable disease (8.0-52.3%). Eribulin monotherapy's safety profile is similar to that of combination therapy. No grade 5 adverse event was reported during monotherapy or in combination with other agents. The grade 4 adverse events reported are neutropenia, leukopenia, thrombocytopenia, anemia, peripheral neuropathy, fatigue, diarrhea, vomiting, dyspnea, back pain, arthralgia, febrile neutropenia, dyspnea, constipation, general physical health deterioration, alopecia. The all-grade adverse events with a percentage above 50% are neutropenia, leukopenia, thrombocytopenia, asthenia, alopecia, elevated AST, elevated ALT, hand-foot syndrome, fatigue, anemia, peripheral neuropathy, oral mucositis, and nausea.